Discovering the Motives to Browse Internet among MBA Students: An Interpretivist Investigation. Issue 3 (September 2018) - Naeem, Usman; Kashif, Muhammad
This study aims to discover motives to browse Internet among MBA students from Pakistan to understand its role to facilitate student leaning in business schools. The data is collected by means of focus groups and Facebook posts to discover motives to browse Internet. Thematic analysis is performed to analyse the data which includes recording, coding, and development of emergent themes. The four motives to browse Internet which are: Communication, Career Management, Information seeking, and Academic performance. The study is unique in two aspects. First, the data triangulation is achieved by methodological advancement to explore the motives behind Internet browsing. Secondly, the business students from a developing Asian country are selected to render some country specific strategies to make productive use of Internet.